Comparative Analysis of Selective Bacterial Colonization by Polyethylene and Polyethylene Terephthalate Microplastics - Song, Yuhao; Zhang, Baoxin; Zou, Lianwei; Xu, Feng; Wang, Yaqi; Xin, Shaoqi; Wang, Yang; Zhang, Hongyuan; Ding, Ning; Wang, Renjun (Frontiers in Microbiology, 2022)
In this study, we report the biodiversity and functional characteristics of microplastic-attached biofilms originating from two freshwater bacterial communities. The results from 16S rRNA amplicon sequencing showed that microplastic-biofilm diversities were mostly determined by original bacteria instead of microplastic types, whereas the biofilm successions on different microplastics were highly dissimilar. Furthermore, the analysis of biomarkers indicated distinct bacterial species with significant dissimilarities between different microplastic-biofilms, which further determined the associated functions. The co-occurrence networks showed distinct interconnective characteristics in different microplastic-biofilms: The structure of microplastic-biofilm incubated in the lake water sample was more robust under environmental stresses, and bacteria in the tap water microplastic-biofilm interacted more cooperatively. Regarding this cooperative interaction, the analysis of functional prediction, in this study, also showed that more symbionts and parasites colonized on microplastics in the tap water than in the lake water. Moreover, it was suggested that microplastic-biofilms were more easily formed in the tap water sample. The overall results revealed significant dissimilarities in bacterial diversity, succession, and associated functions between microplastic-biofilms, in which bacterial species with specific functions should be taken seriously.